Czynnik wpływające na powodzenie sprzedaży ubezpieczeń przez internet - Kaczała, Monika (Factors Affecting Successful Sale of Insurance Over Internet, 2008)
The article attempts to identify factors influencing positive decision regarding purchase of insurance over internet. For this purpose, the article uses presented in the literature results of a research on customers' behaviour in internet which are considered in the context of the specific set of characteristics relating to insurance product. Detailed conclusions are drawn of both theoretical and practical quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 139-146